198k views
5 votes
34x+95=3(14x+9) what is the answer

User Albuvee
by
5.5k points

1 Answer

1 vote

34x+95=3(14x+9)

We move all terms to the left:

34x+95-(3(14x+9))=0

We calculate terms in parentheses: -(3(14x+9)), so:

3(14x+9)

We multiply parentheses

42x+27

Back to the equation:

-(42x+27)

We get rid of parentheses

34x-42x-27+95=0

We add all the numbers together, and all the variables

-8x+68=0

We move all terms containing x to the left, all other terms to the right

-8x=-68

x=-68/-8

x=8+1/2

User Collin Van Dyck
by
5.6k points